OPTIMIZATION OF DIRECTIONAL FRACTURING TECHNOLOGY FOR DIMENSION-STONE PRODUCTION - SHCHIPANOV, IHOR; VOROBYOV, VICTOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper presents an integrated study of controlled directional splitting of monolithic materials driven by soundless chemical demolition agents, in which controlled lateral compression is introduced as an additional governing parameter. We treat the process as a superposition of two fields: the slowly rising expansive pressure inside the borehole, generated by hydration of the mixture, and a quasi-static compressive field uniformly applied to the specimen faces. In this setting, the crack path is dictated not only by local stress concentration near the borehole wall but also by the consistency of boundary conditions with the design splitting plane. The aim is to qualitatively identify ranges in which inter-borehole spacing can be increased without losing crack controllability thanks to moderate lateral compression. The programme is arranged as a parametric study on alabaster prisms; borehole geometry and layout as well as the level of distributed face loading were varied. Baseline drilling parameters were pre-aligned with energy-based criteria for brittle fracture to ensure reproducible initiation. Crack behaviour was assessed by mapping the deviation of the actual split line from the design line along gauge segments. Findings show that even moderate compression planarises the fracture front, suppresses unwanted branching, and reduces edge effects and material heterogeneities. Increasing confinement further stabilises the process, shaping an energetically favourable path within the design plane and broadening the range of rational spacings. A synergy between borehole layout and lateral compression is observed: a suitable choice of diameter, depth, orientation and spacing, combined with uniform pressing, preserves block integrity and improves split surface quality. Practical implications include optimising drilling costs while retaining predictability in vibration- and noise-sensitive environments. Guidance is provided on fixture stiffness, mixture temperature control and loading synchronisation; limitations and a pathway to industrial scaling are outlined.